Gestão pública e participação: uma análise do conselho deliberativo da reserva extrativista Mãe Grande de Curuçá - CHAVES, Aloma Tereza Pinho de Vasconcelos (Universidade Federal do Pará, 2018)
Among the various instruments and democratic public spaces, which emerged in Brazil during the period of political opening and after the 1988 Constitution, are the boards. Although its origin has been from times of great institutional crisis arising from the revolutionary left, Brazil has achieved great democratic status, since the prevailing idea was that citizen participation could indeed resolve the historical problems of the country. The wave environment, experienced in international and national level were created spaces for preservation and conservation, among them, the Extractive Reserves. Built in the midst of a democratic direction, lived in Brazil, the Extractive Reserves configured as a locus of public action by turning to an innovative public administration, composed of elements of civil society and the State. In following the guidelines and democratic demands, the deliberative councils are chosen as the form most appropriate management of space reservations, allowed for the inclusion of sectors previously excluded from any policy making process, the traditional population and guarantee the involvement of the same. However, the territory of the Reserva Mãe Grande consisted Curuçá superimposed on the municipality, which carries low levels of development and has already had its traditional executive power already installed. Such overlapping territories concerned a dispute of political power within the executive branch and between the city and leaders RESEX. As the Reserve will be contending with their public policies, the Deliberative Council of the Reserva Mãe Grande will reach high profile in local dynamic, moving players who step into there to get the prestige arising from that public space.